Impact of FLAMM scoring on cesarean section rate in previous one lower segment cesarean section patient - Patel, Riddhi M.; Kansara, Vijay M.; Patel, Seema K.; Anand, Nikhil (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: The aim of this study was to evaluate the impact of Flamm scoring for Successful VBAC (vaginal birth after cesarean) and Failed TOLAC (Emergency cesarean section) in case of previous one lower segment cesarean delivery. Methods: This is prospective observation study. Out of 150, 111 patients gave consent for TOLAC. 111 patients with previous one caesarean section with gestational weeks between 37 to 40 weeks with spontaneous onset of labour admitted in labour room of Obstetrics and Gynecology Department in Sola Civil Hospital over a period of 1 year from April 2014 to April 2015. Results: In the present study, 111 (74%) patients had undergone TOLAC trial. Out of 111, 77(69.36%) patients had successful VBAC whereas 34 (30.63%) had emergency cesarean. Among the successful VBAC, 7 patients had assisted vaginal delivery to cut short the second stage in prolonged labour. 26% patients refused to give consent for TOLAC from total number of patients in this study. Mean FLAMM score for Successful VBAC was 5.35 (95% CI, 3.9 to 6.7) compared to Failed TOLAC (EME CS) was 3.62 (95% CI, 3.27 to 4.57) Chances of success of TOLAC was increased with increasing FLAMM score according to this study. Conclusions: Application of FLAMM scoring gives fare judgment of successful vaginal birth in TOLAC. So FLAMM scoring can be applied in each previous one lower segment cesarean section patient undergoing TOLAC without increasing morbidity. Practice of protocol of applying FLAMM score and monitoring by partogram will reduce the rate of cesarean section in previous one lower segment cesarean section patient.